Conflitos socioambientais em áreas de preservação permanente: o caso do assentamento Nova Batalha, Vacaria, RS - Peres, Pâmela Corrêa (2012)
No matter what kind of human intervention, it always affects the quality of the environment, especially in areas of high fragility, such as the permanent preservation areas. Thus, the present study seeks to contribute to the understanding of the situation of permanent preservation areas of the settlement “Nova Batalha”, located in the town of Vacaria - RS, by identifying and questioning the environmental conflicts regarding environmental regulations. For such an end, structured interviews, thematic maps and analysis of water quality were used as research instruments, as well as the landscape observation of the family production units. It was found that the permanent preservation areas of the settlement is well preserved, due to the fact that approximately 95.2% are predominant with native vegetation, made of forests and fields. The act of taking care of nature in the settlement is a constant in the speech and practices of families, such as the production of blackberry and raspberry grown with minimal use of pesticides which, other than having an economic motivation, it also reflects the concern to protect natural goods. However, the improper disposal of domestic effluents and the free movement of cattle in the territory, which penetrates some fragments of native forest and permanent preservation areas, are environmental issues that require a more effective intervention from the team providing technical advice to the settlement. The water used for human consumption showed slight contamination with coliforms in 43% of samples, i.e., from the seven samples, three did not meet the legal standards of reference established by the Health Ministry. Given this situation, in order to protect the health of users, it is imperative that measures be implemented to mitigate the pollutants around the water sources.